Simulation Of Conventional Passenger Vehicle Using Engine Map With Different Condition - Hasnal, Ahmad Shazzulhilmi Ahmad (Universiti Sains Malaysia, 2017)
This study simulates a backward facing mathematical model of vehicle in Malaysia (Perodua Myvi) with the presence of torque converter model and the simulations is running on different condition. The conditions are normal driving; start and stop; early down shift; early up shift; late down shift and late up shift. Normal driving and start and stop condition for fuel consumption results from the simulation are compared to the experimental fuel consumption of the same vehicle run on the same drive cycle, to verify the mathematical model for Perodua Myvi that was simulated by using Matlab. The drive cycles data are gathered twice at different times of the day based on city roads and high way in the state of Penang and Kedah, Malaysia. The best fuel economy found is the control strategy of start and stop. Simulation and experimental results are comparable, with the average percentage difference of 13.3 % for the vehicle model.